Radioprotective Effects of Vitis vinifera L. Seed against Radiation-Induced Short-Term Memory Loss in Young Adult Wistar Rats - Ayomide Abe; Fatai Balogun; Olugbenga Ayannuga (Iranian Journal of Medical Physics)
Introduction: Brain radiation therapy often results in short-term memory loss that progresses to cognitive impairment. This issue primarily arises from ionizing radiation generating reactive oxygen species, contributing to chronic oxidative stress that can damage brain cells. While dose fractionation, intensity-modulated radiotherapy, and neural stem cell transplantation have demonstrated limited effectiveness, natural plant antioxidants offer a promising alternative. To investigate the potential of these antioxidants in preventing radiation-induced short-term memory loss, this study examined the radioprotective effects of Vitis vinifera L. seeds in Wistar rats. Material and Methods: Seventy-two young adult male Wistar rats were randomly divided into three equal groups. Group A was the control group, while Groups B and C were subjected to 40 Gy of fractionated whole-brain gamma irradiation. Additionally, the rats in Group C received an oral dose of 100 mg/kg/day of Vitis vinifera L. seeds before, during, and after the radiation treatment. Short-term memory and anxiety levels were assessed at weeks 1, 2, 3, and 4 post-irradiation, followed by routine histological analysis. Statistical significance between the groups was evaluated using a T-test and one-way analysis of variance. Results: The study found that group B rats experienced a significant increase in anxiety states, neurodegeneration, and short-term memory loss compared to groups A and C rats (P < 0.005). The comparison between Groups A and C revealed a significant increase in anxiety levels in Group A (P < 0.005). However, there was no significant difference in neurodegeneration, except at week 3 (P < 0.005). Additionally, the results of the memory assessment became significant at the end of weeks two, three, and four (P < 0.005). Conclusion: Exposure to 40 Gy of fractionated whole-brain gamma irradiation-induced short-term memory loss in rats. However, Vitis vinifera L. seed attenuated the radiation-induced short-term memory loss.